Ribozyme Assays to Quantify the Capping Efficiency of In Vitro-Transcribed mRNA - Irena Vlatkovic; János Ludwig; Gábor Boros; Gábor Tamás Szabó; Julia Reichert; Maximilian Buff; Markus Baiersdörfer; Jonas Reinholz; Azita Josefine Mahiny; Uğur Şahin; Katalin Karikó (MDPI AG, 2022)
The presence of the cap structure on the 5'-end of in vitro-transcribed (IVT) mRNA determines its translation and stability, underpinning its use in therapeutics. Both enzymatic and co-transcriptional capping may lead to incomplete positioning of the cap on newly synthesized RNA molecules. IVT mRNAs are rapidly emerging as novel biologics, including recent vaccines against COVID-19 and vaccine candidates against other infectious diseases, as well as for cancer immunotherapies and protein replacement therapies. Quality control methods necessary for the preclinical and clinical stages of development of these therapeutics are under ongoing development. Here, we described a method to assess the presence of the cap structure of IVT mRNAs. We designed a set of ribozyme assays to specifically cleave IVT mRNAs at a unique position and release 5'-end capped or uncapped cleavage products up to 30 nt long. We purified these products using silica-based columns and visualized/quantified them using denaturing polyacrylamide gel electrophoresis (PAGE) or liquid chromatography and mass spectrometry (LC-MS). Using this technology, we determined the capping efficiencies of IVT mRNAs with different features, which include: Different cap structures, diverse 5' untranslated regions, different nucleoside modifications, and diverse lengths. Taken together, the ribozyme cleavage assays we developed are fast and reliable for the analysis of capping efficiency for research and development purposes, as well as a general quality control for mRNA-based therapeutics.